Proven Portals Best Practices for Planning, Designing, and Developing Enterprise Portals - Sullivan, Dan 1962- (Addison Wesley Professional, 2003)
Annotation
Keywords: Business planning; Strategic planning; Software engineering; Web Sites; Design; Business Enterprises; Computer Networks; Computers; Web; Site Design; Computers; Electronic Commerce; Planification stratégique; Génie logiciel